The future of industrial design in Malaysia / Dr. Marzuki Ibrahim - Ibrahim, Marzuki (2002)
This paper discusses the current development and possible future activities of industrial design in Malaysia. Besides quoting from resources literature review, some of the information provided in this paper is based on the researcher's personal observations and experiences in this field. This paper showed that as Malaysia moves towards the era of modernisation, the government strongly realised the important role of industrial design to the country's industrialisation. For the institutions of higher learning, the government has allocated millions of dollars for the encouragement of research and development (R&D) projects. A comprehensive incentive package has also been set aside to give boost to local industries to enhance the local product development capability. It is hoped that through all these incentives and support given will help to realise the nation's aspiration of becoming fully industrialised by the year 2020. This paper concludes with several proposals that needs to be adopted by four interested parties; namely the government, the industry, the education sector and the general public (consumers) as seen from the industrial designer's perspective.